NH3 release during the evaporation of different types of atmospheric precipitation: A case study in Changchun, China - Xiaoteng Liu; Yingying Xu; Hongsheng Jia; Yunze Zhao; Haodong Hou; Yachao Zhang (Scientific Reports)
Abstract Ammonia (NH3) is a key precursor of secondary inorganic aerosols. During precipitation, NH3 in the atmosphere can be captured by rain and converted to NH4 +, whereas during evaporation, NH4 + can become NH3 and be released again. The northeastern region of China experiences diverse precipitation types, making the study of the NH3 release flux and its influencing factors during evaporation highly significant. In this study, precipitation samples of haze (HZ), dust (DS), convective (CC), and monsoon (MN) events were collected three times in Changchun from March to September 2024 (a total of twelve rain events), and indoor simulation evaporation experiments were conducted. The results revealed significant differences in the NH4 + conversion rate (R), NH3 release flux (F) and release rate (V) across the precipitation types (P < 0.05). The NH3 flux released from precipitation evaporation was 20.33 µg/m2 in spring and 64.53 µg/m2 in summer, accounting for approximately 4.14% and 7.70%, respectively, of the corresponding atmospheric NH3 concentrations. Meteorological factors influenced NH3 release similarly across precipitation types. R peaked and then decreased with increasing temperature and was significantly negatively correlated with wind speed and precipitation amount (P < 0.05). In addition, this study calculates the temperature coefficient (K 1 ), wind speed coefficient (K 2 ), and precipitation amount coefficient (K 3 ) by considering these factors. These findings provide valuable insights for estimating NH3 release fluxes from precipitation evaporation in different regions.